Protecting pollinators : how to save the creatures that feed our world - Helmer, Jodi (Island Press, 2019)
We should thank a pollinator at every meal. These diminutive creatures fertilize a third of the crops we eat. Yet half of the 200,000 species of pollinators are threatened. Birds, bats, insects, and many other pollinators are disappearing, putting our entire food supply in jeopardy. In North America and Europe, bee populations have already plummeted by more than a third and the population of butterflies has declined 31 percent. Protecting Pollinators explores why the statistics have become so dire and how they can be reversed. Jodi Helmer breaks down the latest science on environmental threats and takes readers inside the most promising conservation initiatives. Efforts include farmers reducing pesticides, cities creating butterfly highways, volunteers ripping up invasive plants, gardeners planting native flowers, and citizen scientists monitoring migration. Along with inspiring stories of revival and lessons from failed projects, readers will find practical tips to get involved. They will also be reminded of the magic of pollinators--not only the iconic monarch and dainty hummingbird, but the drab hawk moth and homely bats that are just as essential. Without pollinators, the world would be a duller, blander place. Helmer shows how we can make sure they are always fluttering, soaring, and buzzing around us. -- Provided by publisher.